Medusa's coil - Bishop, Zealia B. (Zealia Brown), 1897-1968; Lovecraft, H. P. (Howard Phillips), 1890-1937 (Salt Lake City, UT : Project Gutenberg, 2023)
"Medusa's Coil" by Zealia B. Bishop and H. P. Lovecraft is a short story first published in January 1939. A traveler seeking shelter at a decaying plantation hears a tale of forbidden love and supernatural horror. When Denis de Russy brings his mysterious Parisian bride Marceline home, dark secrets emerge through a painter's portrait$1 (Brevealing monstrous truths about the woman's true nature and her serpentine hair that possesses its own sinister life. The story blends Lovecraft's Cthulhu Mythos with Greek mythology. (This is an automatically generated summary.)s
Wikipedia page on this work: https://en.wikipedia.org/wiki/Medusa%27s_Coil
Release date is 2023-06-02
Greg Weeks, Mary Meehan and the Online Distributed Proofreading Team at http://www.pgdp.net
Keywords: Horror tales; Missouri -- Fiction